The impact of online archaeological databases on research and heritage protection in Jordan. (2nd January 2017) - Drzewiecki, Mariusz; Arinat, Mahmoud
Abstract : The aim of this study is to understand the contribution of online archaeological databases to research and heritage protection in Jordan. To achieve this a specific set of data was collected by means of a questionnaire survey distributed to archaeologists working in Jordan. A total of 107 researchers completed the form. The results of the survey were analysed and supplemented with information from publications, yearbooks and Jordanian national development strategies. Most of the researchers who replied use archaeological online databases, but have concerns over the reliability of the data. Regarding the impact of the databases on archaeological heritage protection, they are mostly used to record and keep track of the condition of cultural heritage sites. Suggestions for improving databases centred upon the need for regular updates and the creation of a single comprehensive system of data storage.